2013
DOI: 10.1136/oemed-2012-101068
|View full text |Cite
|
Sign up to set email alerts
|

Dust exposure is associated with increased lung function loss among workers in the Norwegian silicon carbide industry

Abstract: Dust exposure, expressed by a quantitative JEM, was found to be associated with an increased yearly decline in FEV1 in employees of Norwegian SiC plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Ulvestad et al (2001) revealed significant decrease in FEV 1 and FVC related to years of exposure. Increasing working years was also related to decreasing annual decline in FEV 1 among silicon carbide industry workers (Johnsen et al, 2013).…”
Section: Lung Functionmentioning
confidence: 85%
“…Ulvestad et al (2001) revealed significant decrease in FEV 1 and FVC related to years of exposure. Increasing working years was also related to decreasing annual decline in FEV 1 among silicon carbide industry workers (Johnsen et al, 2013).…”
Section: Lung Functionmentioning
confidence: 85%
“…An official report of the American Thoracic Society documented the relationship between occupational exposures and an increased risk in chronic cough, lower FEV1, and a lower FEV1/FVC ratio [25]. In addition, dust exposure was found to be associated with a routine decline in FEV1 in workers of Norwegian silicon carbide plants each year [26]. Compared with healthy miners, pulmonary function (FVC, FEV1, FEF50, FEF75, and FEF25–75% of predicted values) declined among miners with CWP, suggesting that changes in pulmonary function parameters are associated with the development of CWP among coal mine workers [27].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 These prior publications expressed spirometric volumes per squared height, and treated dust exposure as a continuous covariate. The available data suggest that a restrictive component of the association between pulmonary function and dust exposure should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that dust exposure in smelters is associated with an accelerated annual decline in lung function 8,9 and with increased prevalence of airflow limitation, 10 indicating an elevated risk of chronic obstructive pulmonary disease. 11 Moreover, our prior findings indicate that increasing dust exposure is positively associated with the incidence of work-related asthma-like symptoms (WASTH) in the absence of doctor-diagnosed asthma.…”
mentioning
confidence: 99%